Comprehensive Hypotheses for Degradation Mechanisms in Ni-Stabilized Zirconia Electrodes. (10th July 2019) - Mogensen, Mogens Bjerg; Chen, Ming; Frandsen, Henrik Lund; Graves, Christopher; Hauch, Anne; Jacobsen, Torben; Jensen, Søren Højgaard; Skafte, Theis Løye; Sun, Xiufu
Abstract : Degradation of nickel-stabilized zirconia (Ni-SZ) electrodes is predominantly due to four features 1) high mobility of Ni, 2) fragile nature of SZ ceramics, 3) narrow three phase boundary (3PB), and 4) effects of impurities: i) in blocking (poisoning of 3PB), and ii) on mobility of Ni. Impurities may be contaminants in reactant gases and influenced by the reactants H2 O, CO2 and CO, or impurities in cell and stack materials. Examples of important degradation types and hypotheses of the degradation mechanisms are described. Examples are: a) loss of electrochemical contact between Ni and YSZ (yttria stabilized zirconia) particles and loss of contact between Ni-Ni particles followed by Ni-migration away from the YSZ electrolyte - one reason is hypothesized being a result of huge potential and thermal gradients at the 3PB; b) growth of Ni-particles; c) redoxing; d) blocking of 3PB and reaction sites by impurities like Si and S. Mitigation methods are discussed.